Image classification using Deep learning - Manoj krishna, M; Neelima, M; Harshali, M; Venu Gopala Rao, M (International Journal of Engineering and Technology, 2018)
The image classification is a classical problem of image processing, computer vision and machine learning fields. In this paper we study the image classification using deep learning. We use AlexNet architecture with convolutional neural networks for this purpose. Four test images are selected from the ImageNet database for the classification purpose. We cropped the images for various portion areas and conducted experiments. The results show the effectiveness of deep learning based image classification using AlexNet.Â Â